2018
DOI: 10.1037/edu0000232
|View full text |Cite
|
Sign up to set email alerts
|

The type of writing instruction and practice matters: The direct and indirect effects of writing instruction and student practice on reading achievement.

Abstract: Previous research has demonstrated that writing instruction can support reading achievement (Graham & Hebert, 2011); however much of this work involved carefully designed interventions. In this study, we evaluated a conceptual framework of the direct and indirect effects of typical writing instruction and student writing practice on reading achievement in first grade. Fall reading, vocabulary, and writing data were collected from 391 students, and classroom writing instruction and student writing practice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…However, classroom reading instruction involves dynamic and complex interactions among teachers and students that cannot be captured by instructional time alone. Considerable evidence suggests that how teachers use time also affects children's literacy achievement (Coker et al, 2018;Connor et al, 2014;Kim et al, 2021). Coker et al (2018) found that certain types of writing instruction in first grade (i.e., composition combined with opportunities to generate texts) predicted students' spring reading achievement.…”
Section: Instructional Time and Children's Reading Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, classroom reading instruction involves dynamic and complex interactions among teachers and students that cannot be captured by instructional time alone. Considerable evidence suggests that how teachers use time also affects children's literacy achievement (Coker et al, 2018;Connor et al, 2014;Kim et al, 2021). Coker et al (2018) found that certain types of writing instruction in first grade (i.e., composition combined with opportunities to generate texts) predicted students' spring reading achievement.…”
Section: Instructional Time and Children's Reading Outcomesmentioning
confidence: 99%
“…Considerable evidence suggests that how teachers use time also affects children's literacy achievement (Coker et al, 2018;Connor et al, 2014;Kim et al, 2021). Coker et al (2018) found that certain types of writing instruction in first grade (i.e., composition combined with opportunities to generate texts) predicted students' spring reading achievement. Connor et al (2014) found that both the quality of teachers' literacy instruction and the amount of time students spent engaging in this instruction interacted to predict third-grade students' reading comprehension and vocabulary gains.…”
Section: Instructional Time and Children's Reading Outcomesmentioning
confidence: 99%
“…The more opportunities students have to practice the material they are being taught, the greater the mastery of the subject matter. In a research study conducted on reading achievement and the practice effect, a small to moderate increase in achievement was found when students were provided with practice opportunities (Coker, Jennings, Farley-Ripple, & MacArthur, 2018). The fatigue effect purports that student learning is negatively affected by fatigue.…”
Section: Limitations and Further Studiesmentioning
confidence: 99%
“…The postgraduate talent training mode based on the "course mode" is represented by the University of Maryland and other universities in the United States: Western universities such as the University of Maryland require postgraduate students to obtain master's degree after completing the specified courses and passing the corresponding course examination, instead of writing and reviewing the master's thesis, the master's postgraduates who are really engaged in scientific research ability training are all arranged for training and training in the doctoral stage (Pacifico et al, 2018;Tabin et al, 2018). The "apprentice mode" is a relatively traditional vocational education mode in Western European universities, represented by Western European institutions of higher learning (Coker et al, 2018;Ran et al, 2018), during reading, students are required to participate in the scientific research work such as related topic experiment, data collection, sorting and analysis, and act as assistants for tutors, Under the guidance of the tutor, finish the writing of the graduation thesis, submit the graduation thesis and carry out the expert review, and obtain the corresponding degree through the defense.…”
Section: The Training Mode Of Postgraduates Need To Be Improvedmentioning
confidence: 99%